Up or down? Capital income taxation in the United States and the United Kingdom - Vito Polito (Center for Economic Studies and ifo Institute (CESifo), 2010)
Empirical evidence suggests that the Effective Marginal Tax Rate (EMTR) on income from capital has increased considerably in both the United States and the United Kingdom over the period 1982-2005. This evidence contradicts the corporate tax literature which predicts that the EMTR should instead fall over time as a result of increasing international capital mobility and higher tax competition between governments. This paper argues that this inconsistency is entirely due to the fact that EMTRs on income from capital are currently computed from versions of the neoclassical investment model which do not take into account financial constraints on dividend policy faced by firms investing in both the United States and the United Kingdom. The paper incorporates financial constraints on dividend policy into the analytical framework for the computation of the EMTR and employs the new model to re-calculate time series of the EMTRs in both countries. The new empirical results show that, in contrast to the existing evidence, the EMTR on investment financed by either retained earnings or new equity has indeed declined over time in both countries, while the EMTR on debt-financed investment has remained relatively stable.
Keywords: H30; 330; capital income taxation; dividend policy; effective marginal tax rates; financial constraints; Kapitalertragsteuer; Optimale Besteuerung; Grenzsteuersatz; Dividende; Verschuldungsrestriktion; USA; Großbritannien